(untitled) (Revista de Investigaciones Universidad del Quindío, 2012)
In the present study we evaluated the morphological development in vitro, callus obtained from nodal seg-ments of young plants of Dendranthema grandiflorum, which were placed in modified MS basal medium in Microsales macrosales and to determine the most modified MS basal medium suitable for growth; six treatments were applied where macrosales varied concentrations and Microsales, half or twice them in different proportions were served containers with 20 mL of culture medium which was supplemented with 1.0 mg / L IAA and 3% sucrose; gelificacnte agent was used as the commercial product Culturegel a rate of 2.8 g / L of medium prepared. The best results were achieved with treatment half-half macrosalts-microsalts relationship, while the double-half treatment showed the lowest growth rates morphological calluses.